2012
DOI: 10.1121/1.3689849
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an additional reflection in a precedence effect experiment

Abstract: Studies on the precedence effect typically utilize a two-source paradigm, which is not realistic relative to real world situations where multiple reflections exist. A step closer to multiple-reflection situations was studied using a three-source paradigm. Discrimination of interaural time differences (ITDs) was measured for one-, two-, and three-source stimuli, using clicks presented over headphones. The ITD was varied in either the first, second, or the third source. The inter-source intervals ranged from 0-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…For longer echo delays, superior performance was obtained for judgments based on the echo, with the difference growing larger with increasing echo delay. Stellmack et al (1999), Litovsky and Shinn-Cunningham (2001), and Goupell et al (2012) have observed this same trend. All found superior performance based on the leading source at delays shorter than 10 ms and better performance based on the lagging echo at longer echo delays [out to 256 ms in Stellmack et al (1999)].…”
Section: A Source Vs Echo Performancesupporting
confidence: 61%
See 3 more Smart Citations
“…For longer echo delays, superior performance was obtained for judgments based on the echo, with the difference growing larger with increasing echo delay. Stellmack et al (1999), Litovsky and Shinn-Cunningham (2001), and Goupell et al (2012) have observed this same trend. All found superior performance based on the leading source at delays shorter than 10 ms and better performance based on the lagging echo at longer echo delays [out to 256 ms in Stellmack et al (1999)].…”
Section: A Source Vs Echo Performancesupporting
confidence: 61%
“…All found superior performance based on the leading source at delays shorter than 10 ms and better performance based on the lagging echo at longer echo delays [out to 256 ms in Stellmack et al (1999)]. Goupell et al (2012) extended this finding to three-pulse stimuli in which judgments were to be based on the first, second, or third. They reported best performance based on the first when the interval between the first and second pulse was less that 10 ms (as long as the lag between the second and third pulses was also less than 10 ms) and best performance based on the third when the interval between the second and third pulse exceeded 10 ms (regardless of the lag between the first and second pulse).…”
Section: A Source Vs Echo Performancementioning
confidence: 69%
See 2 more Smart Citations
“…Correspondingly, leaddominance is viewed as having ended when the two sources were lateralized in equal proportions. Lag-dominance is defined as the preferential localization or lateralization of the lagging source (see also Litovsky and Godar, 2010;Goupell et al, 2012). The sources of lagging sounds are occasionally difficult to localize, a phenomenon referred to as lagdiscrimination suppression.…”
Section: Introductionmentioning
confidence: 99%